Japan's trade policy action or reaction? - Mikanagi, Yumiko (Routledge studies in the growth economies of Asia, 1996)
This book explores the process of policy-making in Japan providing a valuable insight for academics and policy-makers into Japan's massive trade surpluses and the resultant mounting international pressure to resolve the situation.